Overcrowding in the hospital emergency services - Ponce Varillas, Tomás Ignacio (2017)
There is overcrowding of patients in the emergency services of our public hospitals. However, it is a problem that occurs in other countries and appears in the foreign medical literature as crowding. A brief review of the literature is presented discussing time of appearance, causes, consequences and possible solutions. In the absence of national research, sources used were the Comptroller General of the Republic (Contraloría General de la República) on the implementation of and compliance with technical standards in critical areas of 12 public hospitals in Lima and Callao 2012, and the report of the Office of the Ombudsman (Defensoría del Pueblo) on the nationwide inspection of 149 hospitals nationwide in 2012. The gaps between supply of beds and care excess demand in the emergency services inspected and conditions for both inpatients stay and health personnel working in the emergency services are described. Other situations that compromise access and timely attention of people are exposed. The recommendations presented by the two inspecting entities on the congestion of patients within the emergency services are summarized. Overcrowding is a serious public health problem. The main public health providers have to prioritize studies on this matter and propose solutions with plans of development and gradual improvement in the short and medium term.